T cell activation and transplantation tolerance - Priyadharshini, Bhavana (2011)
Transplantation of allogeneic or “non-self” tissues stimulates a robust immune response leading to graft rejection, and therefore most recipients of allogeneic organ transplants require the lifelong use of immune suppressive agents. Excellent outcomes notwithstanding, contemporary immunosuppressive medications are toxic, are often not taken by patients, and pose long-term risks of infection and malignancy. The ultimate goal in transplantation is to develop new treatments that will supplant the need for general immunosuppression. Here we will describe the development and application of costimulation blockade to induce transplantation tolerance and discuss how the diverse array of signals that act on T cells will determine the balance between graft survival and rejection.